The Effect of Dew on in Desert Plant Water Balance in Desert Shrubs - Babu, V Ramesh; Went, Frists W (Annals of Arid Zone, 2016)
Under laboratory conditions dew was found to be taken up by two water stressed Death Valley, California desert plants Tidestromia oblongifolia ( Wats.) Standl, and Atriplex hymenelytra (Torr.) Wats. Recovery from the water stress, upon rewatering was faster in the plants that received dew for 7 hours. During the course of dew availability the plant water saturation deficit and the water potential were rendered favourable for the plants survival and subsequent recovery. It was estimated that in Tidestromia oblongifolia, the water saturaiton deficit was reduced by 38 percent in the old leaves and 32 percent in the young leaves. while in Atriplex hymenelytra the reduction was 19: and 5.5 percent in' old and young leaves' respectively. The rate of water uptake from dew was lower to that observed with water melon (Citrullus vulgaris) and melon (Cucumis melo.) thatare mesophyties.